PRODUCTIVE PERFORMANCE AND ECONOMIC BENEFITS OF BROILER CHICKENS FED GRADED LEVELS OF RICE MILLING WASTE AS REPLACEMENT FOR WHEAT OFFAL - Williams, G.; Doma, U. D.; Abubakar, M.; Bello, K. M.; Jama’a, N.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The experiment was conducted at the Teaching and Research Farm, Department of Animal Production, Abubakar Tafawa Balewa University Bauchi to evaluate the utilization and economic benefits of broiler chicken production using graded levels of rice milling waste (RMW) as replacement for wheat offal in white maize and full fat soya beans-based diets. Five isocaloric and isonitrogenous diets were formulated in which rice milling waste replaced wheat offal at 0, 25, 50, 75 and 100% in diets 1, 2, 3, 4 and 5, respectively at both starter (23% CP) and finisher (20% CP) phases. Three hundred (300) day old chicks were randomly allotted to the five dietary treatments, with four replicates of fifteen birds each in a Completely Randomized Design. Feed and water were given ad libitum throughout the eight weeks period (four weeks of starter and finisher each). Proximate composition of the Rice Milling Waste indicated that it contains 94.12 Dry Matter, 5.21 Crude Protein, 31.40 Crude Fibre, 3.42 Ether Extract, 20.13 Ash and 39.84 Nitrogen Free Extract. Results of the performance parameters showed no statistical significance (P>0.05) in most of the productive performance parameters except feed conversion ratio in finisher (2.81 – 3.72) and overall phases (2.29 – 2.75) which significantly differ at P<0.05. The values of initial weights of birds ranged from 82.07 – 85.65g while that of body weight changes at week four were from 116.60 – 1209. 27g and 1272.70 – 1620.31g for total weight gain. At starter phase, daily feed intake ranged from 68.20 – 70.89g , daily weight gain from 38.64 – 40.15g and feed conversion ratio from 1.72 – 1.83g. In finisher and the overall phases, the values of daily feed intake of 158.71 – 164.11g and 113.45 – 117.50g were obtained while 45.45 – 57.23g and 42.47 – 49.00g for daily weight gain respectively. The total feed cost was lowest in diet 5 (N105.70) and higher in diet 1 (control, N110.46) and the feed cost/kg gain (N) was higher in diet 3 (N555.12) and lower in diet 5 (N 426.72). It was concluded that rice milling waste can completely replace wheat offal in broiler chickens’ diets using white maize and full fat soya bean-based diets without affecting the overall productive performance of the birds with concomitant cost reduction in feed cost and feed cost per kg gain. It is therefore recommended for use in place of the costly wheat offal using white maize and full fat soya bean as sources of energy and protein respectively.